LINGKUNGAN KERJA YANG KONDUSIF DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Aswadi Lubis (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Abstract Conducive working environment allows employees to work more excited so that their work is more satisfying. The work environment is able to provide and improve employee motivation for the work environment has an influence on employees who carry out the work. External factors that affect employee motivation, namely : working conditions, adequate compensation, good supervision, with employment security, status and responsibilities, and flexible rules. Good working environment and clean, get enough light, the exchange of air and a good layout is a work environment that is conducive to creating and improving employee motivation so that organizational goals can be achieved optimally. Create a conducive working environment is very important in the workplace in order to generate productive and innovative performance. The rules still have to be made but with the goal to produce quality performance. Not with the aim of curbing the employees, let alone to kill creativity. Kata Kunci : Lingkungan, Kerja dan Kondisif